2022
DOI: 10.1155/2022/3632053
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Lacidophilin Vaginal Capsules plus rh-IFN-α2b on Efficacy, Vaginal Microecology, and Safety of Patients with HPV Infection

Abstract: Background. Human papillomavirus (HPV) is a self-limiting disease, and there is no specific antiviral drug at present. Purpose. Here, we analyzed the influence of lacidophilin vaginal capsules plus recombinant human interferon α-2b (rh-IFN-α2b) on efficacy, vaginal microecology, and safety of patients with HPV infection. Two hundred cases of HPV infection admitted between January 2019 and December 2020 were retrospectively collected. Of them, 90 cases receiving rh-IFN-α2b intervention were assigned to the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Positive results were obtained in terms of restoring the normal vaginal bacterial flora and inhibiting inflammatory factors. [93] Studies are currently underway to evaluate the effectiveness of combining probiotics with chemotherapy. Previous studies have shown that probiotic supplements may reduce the side effects or toxicity of chemotherapy.…”
Section: Vaginal Treatmentmentioning
confidence: 99%
“…Positive results were obtained in terms of restoring the normal vaginal bacterial flora and inhibiting inflammatory factors. [93] Studies are currently underway to evaluate the effectiveness of combining probiotics with chemotherapy. Previous studies have shown that probiotic supplements may reduce the side effects or toxicity of chemotherapy.…”
Section: Vaginal Treatmentmentioning
confidence: 99%
“…Lacidophilin can be an antibacterial factor by generating lactic acid and destroying the bacterial membrane [ 113 ]. The combination of lacidophilin and antitumor IFN-α2b was investigated for treating HPV-infected patients, with significant results in recovering vaginal microecology and inhibiting inflammatory factors [ 114 ].…”
Section: Bacteriotherapy In Cervical Cancer Treatmentmentioning
confidence: 99%